Wavelength Selective Multi‐Material 3D Printing of Soft Active Devices Using Orthogonal Photoreactions. Issue 2 (20th September 2022) - Rossegger, Elisabeth; Strasser, Jakob; Höller, Rita; Fleisch, Mathias; Berer, Michael; Schlögl, Sandra
Abstract: Orthogonal photoreactions provide a unique way to locally and independently control (thermo)mechanical properties and functionality of polymer networks simply by choice of the wavelength. Herein, a library of acrylate functional coumarin monomers is synthesized, which are cured by sequence‐dependent wavelength orthogonality. In the presence of a long wavelength absorbing photoinitiator, the monomers undergo rapid curing by visible light induced radical chain growth polymerization. Subsequent irradiation with light in the UV‐A region selectively initiates the [2+2] photocycloaddition of the coumarin chromophores, which is confirmed by FTIR and UV–vis experiments. Through a well‐targeted design, acrylate‐based and thiol‐acrylate resin formulations are prepared, whose fast curing rate, low viscosity, and prolonged storage stability enable the one‐step fabrication of multi‐material structures by digital light processing (DLP) 3D printing. By using a dual‐wavelength printer, which operates at two different wavelengths (405 and 365 nm), objects comprising soft ( ε = 22%, σ = 7.5 MPa) and stiff ( ε  = 2%, σ = 8.3 MPa) domains are printed with a single resin vat. Along with tensile properties, the wavelength selective change in the network structure features a local control of the glass transition temperature ( ΔT g  = 17 °C) in the 3D‐printed objects. Soft active devices are fabricated by dual‐wavelength DLP 3D printing, with distinct domains having a higher T g and the local programming of multi shapes is demonstrated. Abstract : Orthogonal photocuring of acrylate functional coumarins is exploited to fabricate soft active devices with distinct soft (405 nm) and stiff domains (365 nm) by dual‐wavelength 3D printing with a single resin vat. The expansion to thiol‐acrylate networks demonstrates the versatility of the concept in generating multi‐material 3D structures and their local shape programming.